Pengembangan Keprofesian Berkelanjutan (PKB) pada Guru SMK Bidang Keahlian Administrasi Perkantoran di Kabupaten Sidoarjo - Siti Sri Wulandari; Bambang Suratman; Jaka Nugraha (IKIP PGRI Bojonegoro, 2020)
Abstrack : The purpose of this research is to describe the characteristics of the implementation of the Sustainable Professional Development Program (PKB) for Vocational School teachers in the Office Administration expertise in Sidoarjo Regency, and to analyze the needs of the Sustainable Professional Development Program (PKB) for Vocational School teachers in the Office Administration expertise in Vocational School in Sidoarjo Regency. The subjects of this research were Vocational School teachers in Office Administration expertise that had received teacher certification in Sidoarjo Regency, namely 35 teachers from several schools in Sidoarjo Regency. The collected data then analyzed using descriptive qualitative data analysis. The conclusion of this research is the implementation of Vocational School Teacher in Sidoarjo regency especially in the field of Office Administration expertise has not been implemented thoroughly, especially the implementation of publications and there are still obstacles faced by certified teacher educators in implementing PKB.Keywords : Sustainable Professional Development (PKB), Teacher Performance.Â Â Abstrak : Tujuan dari penelitian ini adalah untuk mendeskripsikan karakteristik pelaksanaan Program Pengembangan Keprofesian Berkelanjutan (PKB) bagi guru-guru SMK bidang keahlian Administrasi Perkantoran di Kabupaten Sidoarjo, dan menganalisis kebutuhan Program Pengembangan Keprofesian Berkelanjutan (PKB) bagi guru-guru SMK bidang keahlian Administrasi Perkantoran di SMK di Kabupaten Sidoarjo. Subjek penelitian ini adalah adalah guru SMK bidang keahlian Administrasi Perkantoran yang sudah mendapat sertifikasi guru di kabupaten Sidoarjo yaitu 35 guru dari beberapa sekolah di kabupaten Sidoarjo. Data yang telah terkumpul selanjutnya dianalisis menggunakan analisis data deskriptif kualitatif. Kesimpulan dari penelitian ini adalah pelaksanaan PKB guru SMK di Kabupaten Sidoarjo khususnya bidang keahlian Administrasi Perkantoran masih belum terlaksana secara menyeluruh, khusunya pelaksanaan publikasi serta masih terdapat kendala yang dihadapi guru-guru bersertifikat pendidik dalam melaksanakan PKB.Â Kata Kunci : Pengembangan Keprofesian Berkelanjutan (PKB), Kinerja Guru